2019
DOI: 10.1111/tesg.12347
|View full text |Cite
|
Sign up to set email alerts
|

Growing Cities in Sub‐Saharan Africa: Land Competing Interests in Peri‐Urban Areas and Organised Violence

Abstract: Competing interests over land are sharply rising worldwide; they are pushed by several factors, including peri-urban dynamics and growing commercialisation of land. Through a quasiexperimental design based on spatially disaggregated data, the analysis explores the effect of peri-urbanisation processes and large-scale land acquisitions on the risk of organised violence. The results, confirmed throughout several model specifications and robustness checks, provide evidence that peri-urbanisation processes are str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As in other African cities (see Balestri ), peri‐urban areas have been the cradle for slum development and informal settlements. In Arabic, these informal settlements are called ashwaeyat , which literally means ‘randomly built housing’, or the occupation of land without permission to live there or to build.…”
Section: Government Response To Informal Urban Sprawl In Peri‐urban Kmentioning
confidence: 94%
See 1 more Smart Citation
“…As in other African cities (see Balestri ), peri‐urban areas have been the cradle for slum development and informal settlements. In Arabic, these informal settlements are called ashwaeyat , which literally means ‘randomly built housing’, or the occupation of land without permission to live there or to build.…”
Section: Government Response To Informal Urban Sprawl In Peri‐urban Kmentioning
confidence: 94%
“…Researchers from the Food and Agriculture Organisation of the United Nations (FAO) have defined land governance as ‘the rules, processes and structures through which decisions are made about access to land and its use, the manner in which the decisions are implemented and enforced, the way that competing interests in land are managed’ (Palmer et al ). In a peri‐urban context, we can see that different governance structures overlap and that urban expansion is often very chaotic, because powerful plans to restructure these transition zones are often lacking (Balestri ). Due to institutional fragmentation, legal pluralism and overlapping jurisdictions (Evers & de Vries ; Ros‐Tonen et al ), hybrid approaches arise to deal with the different socio‐economic developments and the heterogeneity of land dynamics in these territories.…”
Section: The Inclusive Urban City Debate and The Role Of Peri‐urban Lmentioning
confidence: 99%
“…and has shown that the transforming governance/institutional framework is often marked by sectorial approaches, overlapping jurisdictions, legal pluralism, regulatory confusion, and institutional gaps (Allen, 2014; Friedmann, 2016; Ros‐Tonen et al., 2015; Sawyer, 2014). Recently, studies have focused on aspects of governance, including: land (Balestri, 2019; Jensen et al., 2019; Labbé, 2016; Myers, 2008; Narain, 2009; Shatkin, 2016; Sood, 2021; Trefon, 2009; Zhu, 2013), water (Adams & Zulu, 2015; Aguilar & López, 2009; Allen et al., 2017; Butsch et al., 2021; Hui & Wescoat, 2019; Narain & Singh, 2019; Sreeja et al., 2017), and the connections between land and water (Bartels et al., 2018; Narain, 2014; Sreeja et al., 2017; Vij et al., 2018). …”
Section: Defining the Peri‐urban: State Of The Fieldmentioning
confidence: 99%
“…land (Balestri, 2019; Jensen et al., 2019; Labbé, 2016; Myers, 2008; Narain, 2009; Shatkin, 2016; Sood, 2021; Trefon, 2009; Zhu, 2013),…”
Section: Defining the Peri‐urban: State Of The Fieldmentioning
confidence: 99%